Activation of microglial P2Y12 receptor is required for outward potassium currents in response to neuronal injury. (24th March 2016) - Swiatkowski, P.; Murugan, M.; Eyo, U.B.; Wang, Y.; Rangaraju, S.; Oh, S.B.; Wu, L.-J.
Graphical abstract: Schematic representation showing that the ATP, ADP and UDP released following neuronal injury directly/indirectly act on microglial P2Y12 receptor, a G-protein-coupled receptor linked to a potassium channel, eliciting an outward potassium current. Inhibitors of G-proteins blocked the P2Y12 receptor-mediated outward potassium current. Moreover, this outward current was found to be sensitive to certain potassium channel blockers such as quinine and bupivacaine, while being insensitive to TEA and 4-AP. Arrow-headed lines and bar-headed lines to indicate activation and inhibition, respectively. Dotted lines represent hypothetical associations. Highlights: Microglial P2Y12 receptor mediates ATP/ADP/UDP-induced process chemotaxis and outward K currents. Microglial P2Y12 receptor is coupled to K channel via Gi/Go signaling. Microglial P2Y12 receptor-mediated K channel is sensitive to quinine and bupivacaine. Neuronal injury induces P2Y12 receptor-dependent K currents in microglia. Abstract: Microglia, the resident immune cells in the central nervous system (CNS), constantly survey the surrounding neural parenchyma and promptly respond to brain injury. Activation of purinergic receptors such as P2Y12 receptors (P2Y12R) in microglia has been implicated in chemotaxis toward ATP that is released by injured neurons and astrocytes. Activation of microglial P2Y12R elicits outward potassium current that is associated with microglial chemotaxis in response to injury. This study aimed at investigating the identity of the potassium channel implicated in microglial P2Y12R-mediated chemotaxis following neuronal injury and understanding the purinergic signaling pathway coupled to the channel. Using a combination of two-photon imaging, electrophysiology and genetic tools, we found the ATP-induced outward current to be largely dependent on P2Y12R activation and mediated by G-proteins. Similarly, P2Y12R-coupled outward current was also evoked in response to laser-induced single neuron injury. This current was abolished in microglia obtained from mice lacking P2Y12R. Dissecting the properties of the P2Y12R-mediated current using a pharmacological approach revealed that both the ATP and neuronal injury-induced outward current in microglia was sensitive to quinine (1 mM) and bupivacaine (400 μM), but not tetraethylammonium (TEA) (10 mM) and 4-aminopyridine (4-AP) (5 mM). These results suggest that the quinine/bupivacaine-sensitive potassium channels are the functional effectors of the P2Y12R–mediated signaling in microglia activation following neuronal injury.